Variations in Phytoplankton Primary Production Driven by the Pacific Decadal Oscillation in the East/Japan Sea. Issue 10 (10th October 2022) - Lee, Dabin; Kang, Jae Joong; Jo, Naeun; Kim, Kwanwoo; Jang, Hyo Keun; Kim, Myung Joon; Kim, Yejin; Park, Sanghoon; Son, SeungHyun; Kwon, Jae‐Il; Yun, Mi Sun; Kang, Chang‐Keun; et al.
Abstract: The Pacific Decadal Oscillation (PDO) regime is a major factor not only for the physical properties of the ocean but also for fishery and water resources. However, only a few studies have examined the impact of the PDO on the marine ecosystem in the East/Japan Sea. Therefore, in this study, the relationship between PDO and primary production (PP), and subsequent effects on the marine ecosystem were investigated in the East/Japan Sea using satellite data sets. PDO index showed a negative relationship with sea surface temperature (SST) and the contribution of the small phytoplankton to the total PP during the study period, whereas the mixed layer depth (MLD) and the PP showed a positive relationship with PDO index. The shallower MLD during the negative PDO phase indicates that vertical mixing may be weakened due to the stronger stratification caused by the higher SST than observed during the positive PDO phase. Consequently, we hypothesized that weakened vertical mixing may reduce nutrient supply to the euphotic layer, providing small‐sized phytoplankton favored environmental conditions during the negative PDO. It is noteworthy that PDO‐induced shoaling of the MLD was mainly observed in winter, which may influence the annual PP of the following year. This study shows that the annual PP in the East/Japan Sea can be largely affected through interactions between SST, MLD and subsequent changes in nutrient regime according to the PDO regime, which subsequently affects potential fishery resources in the East/Japan Sea. Plain Language Summary: Pacific Decadal Oscillation (PDO) is very important climatological factor that can affect ocean environmental conditions and its various components. However, only a few studies were conducted to examine the impact of the PDO on the marine ecosystem in the East/Japan Sea. In order to understand how the marine ecosystem will change according to the PDO in the East/Japan Sea, we investigated changes in marine environmental conditions according to the PDO using satellite data sets. Sea surface temperature was warmer, and mixed layer depth was shallower during the negative phase of the PDO. In addition, total primary production of phytoplankton was lower, while the contribution of small‐sized phytoplankton to the total primary production was higher during the negative phase. The higher ocean surface temperature and shallower mixed layer depth suggest that the ocean is more stratified, which can lead to weakening of vertical mixing. Weakened vertical mixing may reduce nutrient supply to the euphotic layer, providing small‐sized phytoplankton favored environmental conditions. Primary production of phytoplankton in the East/Japan Sea can be affected through environmental changes in related to the PDO, which can subsequently affect potential fisheries in the East/Japan Sea. Key Points: Various marine environmental conditions in the East/Japan Sea were closely related to the Pacific Decadal Oscillation (PDO) Primary production and phytoplankton community structure in the East/Japan Sea could be changed according to the PDO A conceptual model for the responses of phytoplankton and potential changes according to the PDO phase in the East/Japan Sea was suggested